Mailart a mime conformant e-mail user agent running on MS Windows - Abcejo, Maria Theresa Ella (1996)
History cannot fully explain man's need to express himself. No wonder that even with the advent of digital machines, called computers, man still sought to use it as a communication tool. It was only a matter of time that isolated systems were connected to each other to make way for multiple users to interact with each other. Among the benefits brought about by networking is facilitated communications, the most popular of which is the electronic mail. This study aims to present a comprehensive evaluation of existing mail systems and to study the network protocols of sending and retrieving electronic mail. It also illustrates the foundations needed in building a user mail agent system. The researchers believe that this study is significant for network users so that the study of major network protocols may be given the attention it deserves. The study will also benefits e-mail users, so that they know what to look for in a mailing system.